Activation of the K(ATP) channel by Mg-nucleotide interaction with SUR1. - Proks, P; De Wet, H; Ashcroft, F (2010)
The mechanism of adenosine triphosphate (ATP)-sensitive potassium (K(ATP)) channel activation by Mg-nucleotides was studied using a mutation (G334D) in the Kir6.2 subunit of the channel that renders K(ATP) channels insensitive to nucleotide inhibition and has no apparent effect on their gating. K(ATP) channels carrying this mutation (Kir6.2-G334D/SUR1 channels) were activated by MgATP and MgADP with an EC(50) of 112 and 8 µM, respectively. This activation was largely suppressed by mutation of the Walker A lysines in the nucleotide-binding domains of SUR1: the remaining small (∼10%), slowly developing component of MgATP activation was fully inhibited by the lipid kinase inhibitor LY294002. The EC(50) for activation of Kir6.2-G334D/SUR1 currents by MgADP was lower than that for MgATP, and the time course of activation was faster. The poorly hydrolyzable analogue MgATPγS also activated Kir6.2-G334D/SUR1. AMPPCP both failed to activate Kir6.2-G334D/SUR1 and to prevent its activation by MgATP. Maximal stimulatory concentrations of MgATP (10 mM) and MgADP (1 mM) exerted identical effects on the single-channel kinetics: they dramatically elevated the open probability (P(O) > 0.8), increased the mean open time and the mean burst duration, reduced the frequency and number of interburst closed states, and eliminated the short burst states. By comparing our results with those obtained for wild-type K(ATP) channels, we conclude that the MgADP sensitivity of the wild-type K(ATP) channel can be described quantitatively by a combination of inhibition at Kir6.2 (measured for wild-type channels in the absence of Mg(2+)) and activation via SUR1 (determined for Kir6.2-G334D/SUR1 channels). However, this is not the case for the effects of MgATP.